Substance and Drug Abuse in The Bahamas and the Caribbean, 1970-2017: A Bibliography - Pinder-Darling, Antoinette P.; Ballance, Virginia C. F. (International Journal of Bahamian Studies, 2017)
An objective for the compilation of this bibliography is to provide a list of resources that address substance and drug abuse in The Bahamas and the wider Caribbean from its beginnings in the 1980s to present day by medical professionals, academics, policy makers and government officials. Therefore, research was conducted to compile as full a bibliographic listing of resources as possible, including links for digital documents. This bibliography does not include everything written about drug and substance abuse in The Bahamas and Caribbean, but it is a guide and starting point for researchers.